P180 Managing pregnancy in pulmonary hypertension using a multi-professional approach: a 16-year experience in a specialist referral centre. (15th November 2017) - Klooster, L ten; Wilson, V; Selby, K; Newton, R; Gandhi, S; Bonnet, T; Fletcher, J; Armstrong, I; Martin, L; Hamilton, N; Mills, G; Thompson, R; et al.
Abstract : Background: Pulmonary hypertension (PH) in pregnancy is associated with a high risk of maternal death (30%–50%). Despite risks, patients may actively plan pregnancy. Patients may also present whilst pregnant with previously undiagnosed PH. Methods: Retrospective review of patients presenting during pregnancy at a PH centre between 2001 and 2017. Results: A total of 27 patients were identified over a 16 year period from 2001 till April 2017. Patients were classified as WHO group 1 (n=25) or group 4 (n=2). Eight of the 27 patients had 2 or more pregnancies and in total 36 pregnancies were managed during the study period. Of the 36 pregnancies, 20 resulted in live birth, 9 ended with medical termination and 7 resulted in a miscarriage. All patients were supervised by a multi-professional team (PH physicians, anaesthetists, obstetricians, intensivists and nurse specialists). 19 deliveries were by Caesarean section with 1 vaginal delivery and planned between 32 to 36 weeks; the earliest live birth was at 25+5 weeks post cardiorespiratory arrest at 25 weeks. Patients underwent epidural or combined spinal/epidural regional anaesthesia and were monitored peri-delivery in an intensive care environment with arterial and central venous access. Of 36 pregnancies, 2 women died within 6 months of delivery (3 and 28 days post-delivery) and none during pregnancy. Patients were followed until January 2017; mean follow up 64 months (range 0–174 months) after last pregnancy. The 5 year survival for all patients (n=27) from date of last pregnancy with PH was 92%. Conclusion: Mortality of PH in pregnancy in a setting of experienced and coordinated care is less than historical series but remains significant. Counselling women with PH of these risks remains an essential part of disease management. In the event of pregnancy, patients should be managed by a multiprofessional team with peripartum care in an intensive care environment.